2007
DOI: 10.1093/ndt/gfm599
|View full text |Cite
|
Sign up to set email alerts
|

The practical implications of using standardized estimation equations in calculating the prevalence of chronic kidney disease

Abstract: Background. Kidney Disease Outcomes Quality Initiative (KDOQI) chronic kidney disease (CKD) guidelines have focused on the utility of using the modified four-variable MDRD equation (now traceable by isotope dilution mass spectrometry IDMS) in calculating estimated glomerular filtration rates (eGFRs). This study assesses the practical implications of eGFR correction equations on the range of creatinine assays currently used in the UK and further investigates the effect of these equations on the calculated preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…The NKDEP recommends that clinical laboratories using creatinine methods that have been calibrated to IDMS should use the IDMS-MDRD equation [27]. Several studies have demonstrated that the IDMS-MDRD equation provides better estimates than the MDRD equation [24,30,34]. …”
Section: Discussionmentioning
confidence: 99%
“…The NKDEP recommends that clinical laboratories using creatinine methods that have been calibrated to IDMS should use the IDMS-MDRD equation [27]. Several studies have demonstrated that the IDMS-MDRD equation provides better estimates than the MDRD equation [24,30,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Improved accuracy of eGFR is obtainable by using isotope dilution mass spectrometry correction especially in the early stages of chronic kidney disease. 16 Non-standardized creatinine measurements from different laboratories may differ systematically by as much as 27 mmol l À1 . 17 A difference of this magnitude would have a large effect on the results of the eGFR equations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 most UK laboratories were using the '175-constant' formula with an IDMS-aligned serum creatinine assay. It has been shown that there is little inter-laboratory variation at more advanced stages of CKD [7].…”
Section: Ukrr Pre-rrt Study Methodsmentioning
confidence: 99%